Performance Management and Quality of Services Offered by Lecturers in Makerere University - Anyango, Mary; Kamaduka, Regis Z.; Kaahwa, Goretti M. (African Journal of Education,Science and Technology (AJEST), 2022)
The aim of the study was to establish the relationship between performance management and quality of services offered by lecturers at Makerere University. It was based on two objectives; to establish the relationship between staff appraisal and effective rewards on quality of lecturers’ services. The researcher used a mixed methodology involving 179 lecturers for collecting quantitative data and five heads of department for collection of qualitative data. Simple random and purpose techniques were used for quantitative and qualitative data collection respectively. Data collection was carried out using a self-administered questionnaire and interview guide. The data collected were analyzed using frequencies, percentages, means and standard deviations at descriptive level while at bivariate level, simple linear regression method was applied. Findings revealed a highly positive significant relationship between staff appraisal and effective rewards on quality of lecturers’ services. It was concluded that performance management dimensions significantly relate positively with quality of services offered by lecturers at Makerere University. The recommendations were as follow; to enhance quality of services offered by lecturers at Makerere University, lecturers and other stakeholders for instance Heads of Department be involved in the appraisal system and appropriately use this appraisal information and feedback in decision making. The reward systems to lecturers be adjusted and improved to match with that of the international standard employees’ rewards in other universities. By doing so, the quality of services offered by lecturers may improve in the university.